Genome annotation [electronic resource] - Soh, Jung; Gordon, Paul M. K. (Paul-Michael Kempton), 1976-, author; Sensen, C. W. (Christoph W.), author (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
Includes bibliographical references and index